2007
DOI: 10.1007/s00421-007-0607-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercises on biophoton emission of the wrist

Abstract: Using two photomultiplier tubes (PMT), we measured the biophoton emission of the left and right wrists simultaneously. The subjects performed hand-grip exercises with both hands, during the measurements. We found a slow increase of the emission rates during the exercises, rising in average from 51.6 cps (counts per second) to 72.3 cps and an immediate decrease after the ending of the exercises. Simultaneous measurement of the skin temperature near the wrist using a thermocouple showed steady increase of temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Of the 56 included studies, 28 were characterized as observational and descriptive studies, out of which 20 studies used whole body[56], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], 3 blood cells[85], [86], [87], 3 saliva[64], [88], [89], 1 blood plasma[90], and 1 breath[91] as systems of research. The details of these studies will be reported on in future publications.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 56 included studies, 28 were characterized as observational and descriptive studies, out of which 20 studies used whole body[56], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], 3 blood cells[85], [86], [87], 3 saliva[64], [88], [89], 1 blood plasma[90], and 1 breath[91] as systems of research. The details of these studies will be reported on in future publications.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of our model, the emitters are triplet excited carbonyl, singlet and triplet excited pigments and singlet oxygen. There are several publications showing the modulation of UPE, relative to the free radicals and excited molecules [such as reactive oxygen species (ROS)] [20,21,[37][38][39][40]. The exact biochemical mechanisms were explained recently by Pospíšil [26].…”
Section: The Emittersmentioning
confidence: 99%
“…We now can set our fist postulate: The signal is present and can in a second time be modulated by the cells. As for example: higher ATP production produces higher ROS concentration, which creates more photons [20,44]. We will look at more ways to modulate the signal in the next paragraph.…”
Section: The Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous ultra-weak photon emission in the order of 10 −16  W/cm 2 is known to be emitted from various living systems comprising of microbial, plant and animal species1234. In the past decades, one-dimensional detection of ultra-weak photon emission was performed using low-noise photomultiplier tube (PMT)5678.…”
mentioning
confidence: 99%